Analisis Doa Daniel Memohon Belaskasihan Tuhan Berdasarkan Daniel 9:1-19 dan Implikasinya Bagi Kehidupan Orang Kristen - Febri Yanto Ziliwu (STT INTI Bandung, 2023)
Prayer is a way of communicating with God, which means that only in prayer can people convey thei struggles or request to God, especially asking for God’s mercy. Awareness of the sins that have been committed, then one way to avoid getting the anger and wrath of God is ti ask God’s mercy through prayer. This paper is written to analyze Daniel’s prayer for God’s mercy based on the book of Daniel 9:1-19 and obtain it’s implications for Christians. In making thins paper, the method used is descriptive-qualitative method, which is to reveal a meaning and produce a view or interpretation of tha text being studied, before God, acknowledge God’s justice, and then ask God’s mercy